Adolescent Premarital Sexual Behavior - Setiana Judith Lopes; Dian Lestari Anakaka; Diana Aipipidely (Universitas Nusa Cendana, 2020)
Abstract. Premarital sexual behavior is the behavior that is driven by sexual desire, both with the opposite sex or same sex without going through a legal marriage process according to law and religion. This study aims to describe premarital adolescent sexual behavior based on sex, age and education level. The design in this study is descriptive quantitative by collecting data from premarital sexual behavior scale (consisted of 11 items) compiled by Widowati (2009). The participants were 400 teenagers aged 17-24 years, currently or have been dating, unmarried, and domiciled at Kelapa Lima Sub District. Data analysis by kruskall-wallis test. The result showed that there are significant differences in premarital adolescent sexual behavior based on sex and age, but there is no significant difference in adolescent sexual behavior based on education level. The teenagers are expected to be able to maintain their behavior and filter information received from peers or the mass media.